Neuronal Network Dynamics in 2D and 3D in vitro Neuroengineered Systems - Frega, Monica (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
The book presents a new, powerful model of neuronal networks, consisting of a three-dimensional neuronal culture in which 3D neuronal networks are coupled to micro-electrode-arrays (MEAs). It discusses the main advantages of the three-dimensional system compared to its two-dimensional counterpart, and shows that the network dynamics, recorded during both spontaneous and stimulated activity, differs between the two models, with the 3D system being better able to emulate the in vivo behaviour of neural networks. The book offers an extensive analysis of the system, from the theoretical background, to its design and applications in neuro-pharmacological studies. Moreover, it includes a concise yet comprehensive introduction to both 2D and 3D neuronal networks coupled to MEAs, and discusses the advantages, limitations and challenges of their applications as cellular and tissue-like in vitro experimental model systems. < .